2013
DOI: 10.1038/eye.2012.277
|View full text |Cite
|
Sign up to set email alerts
|

Endophthalmitis caused by Acinetobacter baumanni: a case series

Abstract: Purpose To profile the etiology, clinical outcomes and drug sensitivity patterns in endophthalmitis caused by Acinetobacter baumanni. Methods Retrospective analysis of all the cases of Acinetobacter baumanni endophthalmitis presenting to tertiary referral care ophthalmic hospital in Eastern India from January 2009 to December 2011 were done. Results A total of four cases were included in the study. Out of the four cases one was post traumatic and the rest were post cataract surgery. All the cases underwent vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 3 publications
(1 reference statement)
0
12
0
Order By: Relevance
“…Acinetobacter spp. is a rare cause of endophthalmitis (Roy et al, 2013), but these cases almost always have a poor anatomical and visual outcome. Acinetobacter spp.…”
Section: Experimental Models: Bench To Bedsidementioning
confidence: 99%
“…Acinetobacter spp. is a rare cause of endophthalmitis (Roy et al, 2013), but these cases almost always have a poor anatomical and visual outcome. Acinetobacter spp.…”
Section: Experimental Models: Bench To Bedsidementioning
confidence: 99%
“…Chen et al 2 has reported two cases, one was endogenous and other was post keratoplasty with outcome of 20/60 in 1 case and No PL in other. While out of four cases reported by Roy R et al3 three were post cataract surgery and one post trauma and they could salvage only one eye with visual outcome of 20/200. Favourable outcome after good microbiological evaluation and timely performed vitrectomy was reported by G. Biigren et al4 in their case report.…”
mentioning
confidence: 91%
“…Few reports of post cataract endophthalmitis by A.Baumannii are reported in literature, indicating poorer visual and anatomical outcomes in maximum cases, despite intensive management. [1][2][3][4] It is a slow growing gram negative bacterium which is generally an inhabitant of soil, vegetation and aquatic environment. It has emerged as one of the most troublesome pathogens for health care professionals because of its resistance to multiple drugs, as reported in various case series.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All these patients underwent intravitreal antibiotic (Cipro oxacin) and vitreoretinal surgical intervention. Finally, ocular condition of 3 of them deteriorated (one resulted in evisceration, one in phthisic eye and the other one developed retinal detachment, post vitrectomy) and only 1 patients reached to the visual acuity of 20/200(8). Recently a case of Acinetobacter baumanni endophthalmitis has been reported, which resulted from intravitreal Ranibizumab injection(9).…”
mentioning
confidence: 99%